2015
DOI: 10.1007/s11606-015-3462-8
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening for Patients on the Female-to-Male Spectrum: a Narrative Review and Guide for Clinicians

Abstract: Guidelines for cervical cancer screening have evolved rapidly over the last several years, with a trend toward longer intervals between screenings and an increasing number of screening options, such as Pap/HPV co-testing and HPV testing as a primary screening. However, gynecological recommendations often do not include clinical considerations specific to patients on the female-to-male (FTM) spectrum. Both patients and providers may not accurately assess risk for HPV and other sexually transmitted infections, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
149
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 40 publications
1
149
0
2
Order By: Relevance
“…Compared with our previous in-person qualitative data collection on this topic and with this study population (Agénor et al, 2016; McDowell et al, Submitted for Publication; Peitzmeier, Agénor, et al, Submitted for Publication; Peitzmeier, Khullar, et al, 2014; Peitzmeier, Reisner, et al, 2014; Potter et al, 2015), we found that the online focus group format utilized here yielded a type and quality of data collected that would likely not have otherwise been possible using an in-person format. These findings replicate previous methodologic research regarding online focus group discussions (Woodyatt et al, 2016), including with gay and bisexual cisgender males.…”
Section: Discussionmentioning
confidence: 66%
“…Compared with our previous in-person qualitative data collection on this topic and with this study population (Agénor et al, 2016; McDowell et al, Submitted for Publication; Peitzmeier, Agénor, et al, Submitted for Publication; Peitzmeier, Khullar, et al, 2014; Peitzmeier, Reisner, et al, 2014; Potter et al, 2015), we found that the online focus group format utilized here yielded a type and quality of data collected that would likely not have otherwise been possible using an in-person format. These findings replicate previous methodologic research regarding online focus group discussions (Woodyatt et al, 2016), including with gay and bisexual cisgender males.…”
Section: Discussionmentioning
confidence: 66%
“…Health care facilities can be welcoming to transmasculine people by offering reproductive health services and settings that are not branded as “women's health care” and by displaying markers of inclusivity, such as rainbow or transgender pride flags or signage. Facilities can also ensure that education materials are inclusive of transgender individuals, intake forms have gender‐affirming language and response options, and front desk and health care staff are trained to use patients’ correct names and pronouns …”
Section: Discussionmentioning
confidence: 99%
“…Health care facilities should ensure that providers receive training in patient‐centered contraceptive care for people from diverse gender identity and other social backgrounds; they should also create environments, procedures and practices that are inclusive of patients whose gender and other social identities are marginalized, and proactively address gender identity and other forms of bias, discrimination and stigma in clinical settings. These patient‐, provider‐ and system‐level interventions may facilitate the delivery of high‐quality, individualized contraceptive care to transmasculine young adults and address the specific and unique contraceptive concerns and needs of this marginalized and underserved population …”
Section: Discussionmentioning
confidence: 99%
“…At these times, the clinic waiting area is likely to be quieter and can minimise the intimidation of a predominantly female environment. All members of clinic staff should be respectful and gender affirming in their behaviour towards the patient and if any mistakes in communication or documentation are made an apology should be quickly offered . In 2015, a report published by the World Health Organization found that one in five transmen refuse health care because doctors and other medical personnel refer to them as the wrong gender…”
Section: General Gynaecological Problems For Transmen Without Gender mentioning
confidence: 99%